Sequential activation of the 5-HT1 A serotonin receptor and trkB induces the serotonergic neuronal phenotype - Galter, Dagmar; Unsicker, Klaus (Molecular and cellular neuroscience, 2002)
Serotonin (5-HT) is an important factor controlling survival, differentiation, and plasticity of neurons in serotonergic target regions of the brain and has been implicated in major psychiatric and autonomic disorders. Relatively little is known, however, of factors controlling differentiation and plasticity of developing and adult 5-HT neurons. We show now that 5-HT, the 5-HT1A receptor, brain-derived neurotrophic factor (BDNF), and its receptor, trkB, form an auto/paracrine loop for the regulation of the serotonergic phenotype. Serotonin applied to cultures from E14 rat raphe increased numbers of neurons expressing serotonergic markers in a dose-dependent manner. Agonists of the 5-HT1A receptor, BP-554 and 8-OH-DPAT, but not agonists of the 5-HT1B and 5-HT1D receptors, mimicked this effect, while the specific 5-HT1A antagonist, WAY-100635, inhibited it. Serotonin also increased BDNF mRNA and protein in embryonic raphe cultures. Induction of serotonergic markers by serotonin was suppressed by a trkB-IgG fusion protein but not by trkC-IgG. Taken together, our data indicate that serotonin acts on 5-HT1A autoreceptors, causing up-regulation of BDNF, which activates trkB to promote serotonergic phenotype-specific markers.
Gesehen am 24.11.2016
Der Buchstabe A im Titel ist tief gestellt